2016
DOI: 10.1002/tal.1314
|View full text |Cite
|
Sign up to set email alerts
|

Alternative approach to compute shear amplification in high-rise reinforced concrete core wall buildings using uncoupled modal response history analysis procedure

Abstract: The seismic response of the high-rise reinforced concrete (RC) wall structures is really complicated as several vibration modes other than the fundamental mode normally contribute significantly to the response-commonly recognized as 'higher mode effects'. Response spectrum analysis (RSA) procedure, which can account for higher mode effects, is usually employed to compute the seismic design demand for the high-rise structures. Recent studies show that the inelastic seismic force demands obtained from the rigoro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 13 publications
(23 reference statements)
1
12
0
Order By: Relevance
“…In consistence with the FIGURE 7 The cyclic modal pushover curves versus the hysteretic response of idealized nonlinear single-degree-of-freedom (SDF) systems (representing an ith vibration mode) under one ground motion previous studies, [14][15][16] this observation reconfirms that the use of same response modification factor (R) for each vibration mode, as prescribed in the standard RSA procedure, is not appropriate. Figure 8 shows the envelopes of individual modal contributions to story displacements, interstory drift ratios, story shears and story overturning moments obtained from the UMRHA procedure, for all three case study buildings.…”
Section: Analysis Of Nonlinear Responses Using the Umrha And Nlrha mentioning
confidence: 69%
See 2 more Smart Citations
“…In consistence with the FIGURE 7 The cyclic modal pushover curves versus the hysteretic response of idealized nonlinear single-degree-of-freedom (SDF) systems (representing an ith vibration mode) under one ground motion previous studies, [14][15][16] this observation reconfirms that the use of same response modification factor (R) for each vibration mode, as prescribed in the standard RSA procedure, is not appropriate. Figure 8 shows the envelopes of individual modal contributions to story displacements, interstory drift ratios, story shears and story overturning moments obtained from the UMRHA procedure, for all three case study buildings.…”
Section: Analysis Of Nonlinear Responses Using the Umrha And Nlrha mentioning
confidence: 69%
“…However, this procedure requires to perform the multimode pushover analysis of an inelastic structural model and, therefore, can also be viewed as a simplification of the modal pushover analysis (MPA) proposed by Chopra and Goel. [13] More recently, Ahmed and Warnitchai [14] and Mehmood et al [15,16] applied the uncoupled modal response history analysis (UMRHA)…”
Section: Background and Motivationmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies have shown that the UMRHA procedure is able to provide accurate predictions of story shears, story overturning moments, interstory drifts, and floor accelerations. Further details of this procedure and its validation can be seen in Chopra, Chopra and Goel, Ahmed, Ahmed and Warnitchai, Mehmood et al, and Najam and Warnichai . The modal cyclic pushover curves of case study rocking wall (shown in Figure ) are idealized using the suitable bilinear FS hysteretic model and the UMRHA procedure is performed to obtain the individual modal contributions as well as the combined response.…”
Section: A Simplified Mpa Procedures For Rocking Wall Structuresmentioning
confidence: 99%
“…These studies have shown that the UMRHA procedure is able to provide accurate predictions of story shears, story overturning moments, interstory drifts, and floor accelerations. Further details of this procedure and its validation can be seen in Chopra, [46] Chopra and Goel, [25] Ahmed, [42] Ahmed and Warnitchai, [43] Mehmood et al, [44,45] and Najam and…”
Section: Figure 12mentioning
confidence: 99%